Calcium Copper Titanate Particles Based Energy Harvesting and Removal of Pharmaceutical Pollutants - Kushal Ruthvik Kaja; Swayam Aryam Behera; Bhagyashree Das; Sugato Hajra; Swati Panda; Mohamed Ahmed Belal; Naratip Vittayakorn; Binita Nanda; P. Ganga Raju Achary; Hoe Joon Kim (ACS Applied Electronic Materials, 2025)
In this work, calcium copper titanate oxide (CaCu3Ti4O12, abbreviated as CCTO) was processed employing a solid-state reaction. The properties of CCTO were thoroughly characterized using various characterization tools. The CCTO particles layer and polytetrafluoroethylene (PTFE) acted as triboelectric layers, forming a contact and separation-based triboelectric nanogenerator (TENG). TENG, based on CCTO/PTFE, delivered an output of 74 V and 6 μA. TENG was utilized to harvest energy through various human activities, effectively charging capacitors, and was further attached to a pillow to monitor sleep. The study also evaluated the photocatalytic performance of CCTO for the degradation of doxycycline, achieving 87% efficiency within 45 minutes under visible light. The reaction pathway was thoroughly investigated, and catalyst reusability was examined. CCTO demonstrates potential as a dual-function material, serving both as a photocatalyst for environmental cleanup and as a triboelectric material for energy harvesting.
Keywords: Innovative Energy Harvesting Technologies; Advanced Sensor and Energy Harvesting Materials; Energy Harvesting in Wireless Networks